Public Information Policy in the Digital Era and Indonesian Research Trends in the Last Decade - Khumayah, Siti (Journal of Governance, 2025)
: This research examines the trends and developments in public information policy in Indonesia from 2014 to 2024 through a literature analysis of 35 relevant studies. The main focus of the research is to examine how public information policy is evolving in the context of the digital era, as well as the role of technology and social media in improving government transparency and accountability. By identifying key challenges such as lack of information transparency, inequality in public access to data, and issues related to the application of technology in the public sector. This research uses a mixed-methods approach through historical data processing over a period of 10 years, and then descriptive analysis is made on each result obtained. The results found that out of 649 publications over a period of 10 years, Indonesian researchers have contributed research to as many as 35 publication documents that show that the implementation of public information policy in Indonesia has undergone significant transformation thanks to digital technology, although various technical and structural barriers still need to be overcome to increase its effectiveness in supporting better governance. This article aims to provide new insights for researchers, policymakers, and practitioners in formulating more inclusive and data-driven policies.